2018
DOI: 10.14260/jemds/2018/494
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia in Cirrhosis- Prevalence and Correlation With the Complications of Cirrhosis

Abstract: BACKGROUNDHyponatraemia is one of the complications in cirrhotic patients, occurring in more than one-third of the patients with chronic liver disease and is believed to be caused by defective water homeostasis. The objective of our study is to establish the prevalence of hyponatraemia in cirrhosis and to investigate if hyponatraemia predicts a rate of severity of complications in cirrhosis. MATERIALS AND METHODSA cross-sectional study was done in patients diagnosed with cirrhosis by a combination of clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In similar research, Meganathan et colleagues found that ALT, AST, and ALP were not substantially related to serum sodium levels. 12 Elkady et al also found no correlation between ALP, AST, AST, and bilirubin and hyponatremia. Umemura et colleagues discovered that individuals with serum sodium levels of 139 mEq/l had considerably reduced median AST, ALT, GGT, and total bilirubin.…”
Section: Discussionmentioning
confidence: 96%
“…In similar research, Meganathan et colleagues found that ALT, AST, and ALP were not substantially related to serum sodium levels. 12 Elkady et al also found no correlation between ALP, AST, AST, and bilirubin and hyponatremia. Umemura et colleagues discovered that individuals with serum sodium levels of 139 mEq/l had considerably reduced median AST, ALT, GGT, and total bilirubin.…”
Section: Discussionmentioning
confidence: 96%
“…Meganathan and Kumar established the prevalence of hyponatremia in cirrhosis and to investigate if hyponatremia predicts an increased rate and severity of complications in cirrhosis. 9 They reported hyponatremia in 44%, normal serum sodium in 26%, and hypernatremia in 30% of the patients. In another study, Umemura et al, evaluated mortality in cirrhosis patients taking conventional diuretics and identified associations between serum sodium level and clinical characteristics.…”
Section: Dysnatremiamentioning
confidence: 96%
“…Group A Group B Group C (P<0.01) were found to occur significantly more commonly among patients from Group A, as compared to those in patients from Group B or C. In a similar study by Meganathan and Kumar, the majority of the hyponatremic patients had the hepatorenal syndrome. 9 The incidence of portal hypertension was 95% in patients with severe hyponatremia. About 84% of the hyponatremic patients had the hepatorenal syndrome.…”
Section: Complications Of Chronic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation